Typography in film credit sequences / Deniz Faramarzi Asli - Deniz Faramarzi, Asli (2017)
This study presents an investigation of typography as a visual element in context of film opening credits based on principles of visual perception derived from Gestalt psychology and Formalism within film theory. The research will be conducted in an effort to reveal the communicative qualities of typography in film titles as well as the significance of screen based typography as a visual element and its capability to express certain styles and moods in relation to the film. Typography in film credit sequences in previous studies has been considered merely as an informative and denotative element as they have all emphasized on the literal meaning of the type. Therefore there is a lack of analytical study on visual perception and connotative role of typography in the context of film titles based on film theory interpretation. This research was initiated in an effort to further examine the communicative values of typography in film titles based on a theoretical methodology derived from common concepts between Gestalt principles of visual perception and formalism within film theory. The study analyzes various examples of typography in film titles based on categories of the provided theoretical framework which examine typography in five different aspects. The findings of this study emphasize the role of typography as a formal and visual element in film titles in terms of implying certain meanings and signifying the mood of the film; as well as its role as a connotative and figurative element in film title sequences.